Border Effects in House Prices - Martin Micheli; Jan Rouwendal; Jasper Dekkers (Tinbergen Institute, 2014)
We estimate the effect of the Dutch-German border on house prices. In the last 40 years the development of house prices in the Netherlands and Germany has been substantially different. While the Netherlands have been hit by two real estate cycles, prices in Germany have been extraordinary stable. We develop a model for studying house prices and the impact of the border. Then we study the development of Dutch house prices close to the German border in the period 1985-2013. Next, combining German and Dutch real estate datasets, we study the jump in the housing price occurring at the border. Using different estimation strategies, we find that ask prices of comparable housing drop by about 16% when one crosses the Dutch-German border. Given that price discounts from the last observed asking price are substantially larger in Germany, we interpret our findings as indicating the willingness of Dutch households to pay up to 26% higher house prices to live among the Dutch.
Keywords: R31; F15; R21; 330; house prices; European integration; border effects